A survey of buckling of conical shells subjected to axial compression and external pressure - Ifayefunmi, Olawale (2014)
The paper reviews literature on buckling of conical shells subjected to three loading conditions: (i) axial compression only, (ii) external pressure only and (iii) combined loading. The review is from the theoretical as well as experimental points of view. This review covers known experiments on cones from (1958 – 2012). The literature review is split thematically into the following categories: theoretical prediction of axially compressed cones, theoretical prediction of externally pressurized cones, theoretical prediction of cones under combined loading, buckling experiments on axially compressed cones, buckling experiments on externally pressurized cones, buckling experiments on cones subjected to combined loading, buckling experiments on composite conical shells, equivalent cylinder approach, effect of initial geometric imperfection on the buckling behaviour of cones and effect of imperfect boundary conditions on the buckling behaviour of cones.